Hydrogen Sulfide Reduces Cognitive Impairment in Rats After Subarachnoid Hemorrhage by Ameliorating Neuroinflammation Mediated by the TLR4/NF-κB Pathway in Microglia - Duan, Hongzhou; Li, Liang; Shen, Shengli; Ma, Yuanyuan; Yin, Xiangdong; Liu, Zhen; Yuan, Changwei; Wang, Yingjin; Zhang, Jiayong (Frontiers in Cellular Neuroscience, 2020)
Background and Aims: Cognitive impairment is one of the major complications of subarachnoid hemorrhage (SAH) and is closely associated with neuroinflammation. Hydrogen sulfide (H2S) has been shown to have an anti-inflammatory effect and reduce cognitive impairment in neurodegenerative diseases, but its effects in SAH have been little studied. This study aimed to investigate the effects of H2S on cognitive impairment after SAH and the possible underlying mechanisms. Methods: Forty-eight male SD rats were randomly divided into three groups: a sham group, an SAH group, and an SAH+NaHS (an H2S donor) group. The endovascular perforation technique was used to establish the experimental SAH model. NaHS was administered intraperitoneally. An active avoidance test was performed to investigate cognitive function. The expression of TNF-α, TLR4, and NF-κB p65 in the hippocampus was measured by Western blot and immunohistochemistry. The types of cells expressing TNF-α were detected by double immunofluorescence staining. Results: Compared to that in the sham group, the learning and memory ability of rats in the SAH group was damaged. Furthermore, the expression of TNF-α, TLR4, and NF-κB p65 in the hippocampus was elevated in the SAH group (p<0.05). TNF-α was mainly expressed in activated microglia, which was consistent with the expression of TLR4. Treatment with NaHS significantly decreased the cognitive impairment of rats after SAH and simultaneously reduced the expression of TNF-α, TLR4, and NF-κB p65 and alleviated the nuclear translocation of NF-κB p65 (p<0.05). Conclusions: The neuroinflammation reaction in microglia contributes to cognitive impairment after SAH. H2S reduced the cognitive impairment of rats after SAH by ameliorating neuroinflammation in microglia, potentially via the TLR4/NF-κB pathway.